2009
DOI: 10.1302/0301-620x.91b12.22740
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection of the acromioclavicular joint

Abstract: Intra-articular punctures and injections are performed routinely on patients with injuries to and chronic diseases of joints, to release an effusion or haemarthrosis, or to inject drugs. The purpose of this study was to investigate the accuracy of placement of the needle during this procedure.A total of 76 cadaver acromioclavicular joints were injected with a solution containing methyl blue and subsequently dissected to distinguish intra-from peri-articular injection. In order to assess the importance of exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 16 publications
3
18
1
4
Order By: Relevance
“…They found the improvement to be more important in younger patients and in women. 10 This was not confirmed by the data presented in this study, with no significant differences in age between the patients that had or had not improved after the injection.…”
Section: Discussioncontrasting
confidence: 58%
“…They found the improvement to be more important in younger patients and in women. 10 This was not confirmed by the data presented in this study, with no significant differences in age between the patients that had or had not improved after the injection.…”
Section: Discussioncontrasting
confidence: 58%
“…No comparative studies of the hip were identified. Ultrasound was used in seven studies,15,19–21,23,25,26 and the remaining studies utilized air arthrography,17 fluoroscopy,14,16,24 magnetic resonance arthrography,18 or magnetic resonance imaging22 (Table 1). Across all studies (using all imaging modalities and all joints), needle placement accuracy ranged from 63% to 100% with ultrasound and from 39% to 100% with conventional anatomical guidance (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Joint injections guided by palpation has been shown to have an accuracy of 40% to 66% for injecting into the correct compartment, but this is in comparison to the accuracy of 100% that can be achieved using fluoroscopy. 27,28) Ultrasound-guided injection shows an accuracy of 95%…”
Section: Acromioclavicular Joint Injectionmentioning
confidence: 99%